A New Generalization of the Haddock Conjecture - Xiao, Songlin (Mathematical Modelling and Analysis, 2017)
In this paper, we establish some new criteria on the boundedness and asymptotic constancy of solutions for a class of scalar neutral functional differential equations with time-varying delays via differential inequality techniques. Our results are an improvement of existing ones and generalization of the Haddock conjecture.